Gamma-aminobutyric acid improves phenanthrene phytotoxicity tolerance in cucumber through the glutathione-dependent system of antioxidant defense - Guo, Zhixin; Lv, Jingli; Dong, Xiaoxing; Du, Nanshan; Piao, Fengzhi (Ecotoxicology and environmental safety, 2021)
Phenanthrene (PHE), a typical organic pollutant, has drawn attention in recent years due to its toxicity to plants and human health. Gamma-aminobutyric acid (GABA) induce plant tolerance to diverse stresses. However, the role and regulatory mechanisms of GABA in PHE stress responses in plants remains largely uncharacterized. Here, we showed that GABA content increased by 44.5%, 89.2%, 160% and 39.2% under 50, 100, 200 and 300 µM PHE treatment, respectively compared with mock. GABA treatment alleviated PHE-induced growth inhibition in a dose-dependent manner, with the most effective concentration of 50 mM GABA. Although exogenous GABA could not influence the accumulation of PHE in cucumber, it significantly mitigated photosynthetic inhibition and enhanced the transcripts and activities of the antioxidant enzymes such as ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD), resulting in less accumulation of hydrogen peroxide (H2O2) and superoxide (O2.–). Importantly, timecourse analyses of glutathione (GSH) homeostasis showed that GABA markedly increased GSH content and GR activity as well as the transcripts of GSH biosynthesis-related genes GSH1, GSH2 and GR during PHE stress. Conversely, pretreatment with GSH biosynthesis inhibitor buthionine sulfoximine (BSO) abolished the GABA-induced changes in PHE stress. Together, these results suggest that GABA enhances tolerance to PHE stress via a GSH-dependent system of antioxidant defense in cucumber. [Display omitted] •PHE stress induced GABA synthesis in cucumber.•GABA alleviated PHE stress-induced growth and photosynthetic inhibition.•GABA did not affect PHE accumulation but improve ROS scavenging in cucumber.•GABA enhanced tolerance to PHE stress via a GSH-dependent system of antioxidant defense.